The Significance of a Low-residual Diet in Preventing Relapse of Crohn's Disease - Endo, K.; Unoura, A.; Sato, T.; Watanabe, H.; Okata, T. (Nippon Daicho Komonbyo Gakkai Zasshi, 1985)
Recent advances in nutritional and drug treatment of Crohn's disease have made it possible to attain remission in many cases. However, the problem is that once remission is attained, relapse easily occurs after peroral intake of an ordinary diet. Therefore, we ad-ministered a low-residual diet (Hinex-R or Clinimeal) to prevent relapse, and the significance of a low-residual diet in preventing the relapse of Crohn's disease was evaluated. The subjects were 3 male and 2 female patients with Crohn's disease. These patients, who attained remission after nutritional and drug treatment, were administered 400 kcal of the low-residual diet in the morning and at night. Ordinary meals were given at noon and in the evening. Salazopyrin was administered as maintenance therapy. The effects were judged by subjective complaints and laboratory data. It was shown that the low-residual diet was effective in preventing relapse of Crohn's disease in three cases : However, there were two ineffective cases. In the latter cases home hyperalimentation therapy or some other treatment might be indicated.